Why we broke up - Handler, Daniel (Little, Brown, 2011)
Sixteen-year-old Min Green writes a letter to Ed Slaterton in which she breaks up with him, documenting their relationship and how items in the accompanying box, from bottle caps to a cookbook, foretell the end.